Artikel Directive Speech Acts in the Context of Learning: Analysis of the Principle of Cooperation as a Strengthening of Communication Ethics - Syamsiyah Sitisyam; Sudiyana B.; Nurnaningsih (Universitas Pendidikan Ganesha, 2025)
Primary school Indonesian language instruction still faces challenges in fostering effective communication ethics through teacher student interactions. This study aims to analyze directive speech acts and the application of the cooperative principle in strengthening communication ethics in Indonesian language learning. A qualitative case study design was employed, involving teachers and students as participants, with data collected through participant observation, semi structured interviews, and document analysis of classroom interactions. A total of 40 speech acts were analyzed interactively using Miles and Huberman’s model, including data reduction, data display, and conclusion drawing, with data validity ensured through source and method triangulation. The findings identified three classifications of directive speech acts: from teacher to students, students to teacher, and among students, realized through requesting, questioning, and suggesting. The cooperative principle, particularly the maxims of relevance and quantity, dominated teacher interactions, effectively reinforcing communication ethics. The results indicate that consistent application of the cooperative principle enhances politeness, mutual respect, and the ability to maintain positive social relationships in classroom interactions. The study highlights the importance of integrating the cooperative principle in developing pragmatic materials and teaching communication ethics, thereby fostering a culture of effective and civilized communication in primary education.